2018
DOI: 10.1155/2018/1601363
|View full text |Cite
|
Sign up to set email alerts
|

SoxGenes Show Spatiotemporal Expression during Murine Tongue and Eyelid Development

Abstract: The tongue is a critical organ, involved in functions such as speaking, swallowing, mastication, and degustation. Although Sox genes are known to play critical roles in many biological processes, including organogenesis, the expression of the Sox family members during tongue development remains unclear. We therefore performed a comparative in situ hybridization analysis of 17 Sox genes (Sox1–14, 17, 18, and 21) during murine tongue development. Sox2, 4, 6, 8, 9, 10, 11, 12, and 21 were found to be expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…The observed skeletal defects such as micrognathia, broad/full nasal tip, and prominent chin are consistent with SOX5 having a role in chondrogenesis. Sox5 is strongly expressed in Meckel's cartilage in mice (Ishikawa et al, 2018), which could explain the presentation of micrognathia, specifically. The general lack of severity of these craniofacial phenotypes is most likely due to individuals possessing other functional SOXD alleles, which is supported by Sox5 −/− having only minor skeletal defects (Smits et al, 2001).…”
Section: Lamb-shaffer Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…The observed skeletal defects such as micrognathia, broad/full nasal tip, and prominent chin are consistent with SOX5 having a role in chondrogenesis. Sox5 is strongly expressed in Meckel's cartilage in mice (Ishikawa et al, 2018), which could explain the presentation of micrognathia, specifically. The general lack of severity of these craniofacial phenotypes is most likely due to individuals possessing other functional SOXD alleles, which is supported by Sox5 −/− having only minor skeletal defects (Smits et al, 2001).…”
Section: Lamb-shaffer Syndromementioning
confidence: 99%
“…n/a n/a n/a n/a More detailed expression patterns for factors can be found in: (Kawasaki et al, 2015;Watanabe et al, 2016;Ishikawa et al, 2018). Epithelial (Epi), Mesenchymal (Mes), Muscle (Mus), Not expressed (n.e).…”
Section: G Sox15mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study indicated that a reduction in Sox2 expression to 20 % of normal levels causes papilla placodes and early papillae to begin developing but fail to reach maturity, while filiform papillae develop normally [ 46 ]. In contrast, overexpression of Sox2 induces the development of atypical fungiform-like papillae, but filiform papillae do not develop [ 47 ]. This finding suggested that Sox2 regulates the differentiation of endodermal progenitor cells in the mouse tongue into taste bud cells rather than keratinocytes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is different from the expression of SOX2 in the fungiform papilla of mice. Moreover, Sox2 is expressed in the mesenchyme between the superior and inferior longitudinal and genioglossus muscles in the middle and posterior regions of the tongue as well as in the epithelium throughout the tongue [ 47 ]. Therefore, at which stage SOX2 plays a role in the development of tongue fungiform papillae in small pigs is unclear, and its developmental network still needs to be further constructed and explored.…”
Section: Discussionmentioning
confidence: 99%